2021
DOI: 10.1007/s12070-021-02641-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Anosmia among Covid 19 patients in India

Abstract: The pandemic COVID-19 has relentlessly caused havoc to human life since its outbreak in December 2019. The disease has been a challenge for all. The clinical manifestations of Covid-19 ranges from no symptoms at all to severe acute respiratory distress syndrome. Anosmia being one of the important clinical features of COVID-19 has always been overlooked by the Indian population. This formed the background for this study. Aim To identify the incidence of anosmia reported in COVID- 19 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Chemosensory dysfunction in COVID-19 can be assessed by questionnaires and history taking (subjective tests) or by testing the sense of smell objectively. ,, Some studies using objective tests showed an increase in the prevalence of olfactory dysfunction, ,,, while other studies reported the opposite (reviewed in Boscutti et al, 2021) . In the studies on South Asian COVID-19 patients, objective tests were used in only three of the cohorts with G614 virus dominance.…”
Section: Methodsmentioning
confidence: 99%
“…Chemosensory dysfunction in COVID-19 can be assessed by questionnaires and history taking (subjective tests) or by testing the sense of smell objectively. ,, Some studies using objective tests showed an increase in the prevalence of olfactory dysfunction, ,,, while other studies reported the opposite (reviewed in Boscutti et al, 2021) . In the studies on South Asian COVID-19 patients, objective tests were used in only three of the cohorts with G614 virus dominance.…”
Section: Methodsmentioning
confidence: 99%
“…Chemosensory dysfunction in COVID-19 can be assessed by questionnaires and history taking (subjective tests), or by testing the sense of smell objectively. 1,7,93 Some studies using objective tests showed an increase in the prevalence of olfactory dysfunction, 1,2,82,[93][94][95] while other studies reported the opposite (reviewed in Boscutti et al, 2021). 7 In the studies on South Asian COVID-19 patients, objective tests were used in only three of the cohorts with G614 virus dominance.…”
Section: Effects Of Response Bias Age Disease Severity Gender and Methodologymentioning
confidence: 99%
“…Bulk RNA-Sequencing data of the Whole Olfactory Mucosa (WOM) prove the absence in the expression of ACE2 and TMPRSS2 in OSNs, however, the same genes were presented in sustentacular cells. Anosmia is caused due to four underlying mechanisms in COVID-19-positive individuals, namely: rhinorrhea and nasal obstruction: loss of OSNs: invasion of olfactory centres of the brain: and damage to sustentacular cells in the OE (Aanand, P. et al, 2021: Sungnak W. et al, 2020: Brann, D. H. et al, 2020. Anosmia is a common symptom of various intranasal diseases such as rhinosinusitis and nasal polyposis.…”
Section: Ageusia and Anosmia Among Individuals Who Tested Positive Fo...mentioning
confidence: 99%